When Regulation Becomes a Restriction: Examining Zainal Abidin Bagir’s Thoughts on Religious Freedom and Belief in Indonesia - Rasyid, Abd. (Inklusiva: Jurnal Studi Agama-Agama, 2023)
This research would explore the analysis of Zainal Abidin Bagir — Lecturer at the Center for Religious and Cross-Cultural Studies (CRCS) and Director of the Indonesian Consortium for Religious Studies (ICRS), Gadjah Mada University, Yogyakarta — on the dynamics of religious freedom in Indonesia. In order to explain these dynamics, this study uses qualitative methods. These are balanced by direct interviews with Bagir and enriched by other relevant literature. Historical and sociological approaches are useful in clarifying, evaluating and analyzing the factors that cause religious freedom and religious blasphemy regulations to be considered important to implement in Indonesia. The results of this research show that, firstly, the implementation of religious freedom regulations in Indonesia often clashes with the social, cultural and political dynamics prevailing in the country, leading some groups to believe that ‘religious freedom’ is not suitable for implementation in Indonesia. In some instances, this perceived incompatibility has resulted in the rights of minority groups such as Ahmadiyyah and Shia being violated and restricted. Second, Bagir is not in a hurry to judge the state of religious freedom in Indonesia as terrible. In terms of the overall landscape, Bagir said that the religious freedom situation in Indonesia continues to appear relatively well developed and continues to make progress, although it is not totally unproblematic.